2011
DOI: 10.1249/mss.0b013e31820b9395
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Self-Monitoring and Weight Loss

Abstract: Introduction Weight loss has been associated with higher physical activity (PA) levels and frequent dietary self-monitoring. Less is known about how PA self-monitoring affects adherence to PA goals, PA levels and weight change. Methods The SMART Trial is a clinical weight loss trial in which 210 overweight adults were randomized equally to one of three arms: 1) paper record (PR); 2) personal digital assistant with self-monitoring software (PDA); and 3) PDA with daily tailored feedback message (PDA+FB). PA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 27 publications
9
129
0
2
Order By: Relevance
“…It has been demonstrated that ICTbased lifestyle interventions are beneficial helping the patient to reduce body weight, stop using tobacco, and continue exercise training programs. [369][370][371][372] In Australia, the Australian e-Health Research Centre (AEHRC) is conducting a RCT of patients recovering from a MI, comparing an ICT-based cardiac rehabilitation program, in which all elements of cardiac rehabilitation (education, instruction, setting goals, and counseling) are enacted using mobile phones and the Internet, with a conventional homebased cardiac rehabilitation program. 373 Figure 15.…”
Section: Ways To Continue Exercise Training (1) Ways To Maintain Motimentioning
confidence: 99%
“…It has been demonstrated that ICTbased lifestyle interventions are beneficial helping the patient to reduce body weight, stop using tobacco, and continue exercise training programs. [369][370][371][372] In Australia, the Australian e-Health Research Centre (AEHRC) is conducting a RCT of patients recovering from a MI, comparing an ICT-based cardiac rehabilitation program, in which all elements of cardiac rehabilitation (education, instruction, setting goals, and counseling) are enacted using mobile phones and the Internet, with a conventional homebased cardiac rehabilitation program. 373 Figure 15.…”
Section: Ways To Continue Exercise Training (1) Ways To Maintain Motimentioning
confidence: 99%
“…In our study, the attrition rates were 27.3% by T2 and 40.9% by T3. Previous studies, which ranged from 6 weeks to 18 months of self-monitoring, reported attrition rates of 22% to 72% (Burke et al, 2012;Conroy et al, 2011;Donaldson et al, 2013;Hood et al, 2013;Kong et al, 2012;Steinberg et al, 2013;Wing et al, 2006). The longer a study, the higher the attrition rate was.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, self-monitoring with at least one of the other four selfregulatory strategies (prompt intention, specific goal setting, review of behavioral goals, and feedback) are significantly more effective than interventions without these strategies in changing lifestyle behaviors (effect size .54 vs. .24 for healthy eating and .38 vs. .27 for physical activity) (Bird et al, 2013;Michie, Abraham, Whittington, & McAteer, 2009). Among non-pregnant adults who perform self-monitoring, increased frequency of self-monitoring of diet, physical activity, or weight is linked to eating less fat and getting more exercise and to decreased waist circumference and weight loss (Burke et al, 2012;Conroy et al, 2011;Kong et al, 2012).…”
Section: Self-monitoring Of Lifestyle Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, our measure on adherence to self-monitoring of physical activity depended on patient adherence to the recommended physical activity behaviors. While this approach has been used in several other studies [26,33], it may underestimate the actual adherence to self-monitoring of physical activity. For example, our adherence to self-monitoring of physical activity was lower than adherence dietary self-monitoring, which could suggest that participants did not exercise at all on that particular day, they did not bother to enter 0 for exercise minutes, and instead, they left it blank.…”
Section: Discussionmentioning
confidence: 99%